Bilateral agreement for the period 2007/2010 Socrates programme: higher education (Erasmus) between Universidade Lusíada de Lisboa e Universidad de Málaga - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the Socrates programme. - Subject area: Economics.